Exhumation of a Methamphetamine Body Packer: Pitfalls of Hair Result Interpretation. Issue 2 (14th April 2021) - Hakim, Florian; Nassibou, Shanti; Gish, Alexandr; Lima, Benjamin; Wiart, Jean-François; Richeval, Camille; Outreville, Jonathan; Quétard, Véronique; Allorge, Delphine; Gaulier, Jean-Michel
Abstract: Carrying out toxicological investigations in biological samples (e.g., hair) collected from extensively decomposed bodies and interpretation of subsequently obtained results is challenging, even more in some particular circumstances of death. In order to illustrate these pitfalls, we report the case of the exhumation of a methamphetamine (MA) body packer. Autopsy examination of a 41-year-old man, 1 year after his burial, revealed the presence of 44 green pellets (7 out of 44 were torn) along all the gastrointestinal tracts. A 6 cm long dark hair strand and pellets were sampled for toxicological analyses. Large toxicological screenings were applied to hair and pellets using both LC–MS-MS and LC–HRMS. Intact pellets contained around 10 g of MA with a purity ranging from 29 to 35%. Positive hair results were amiodarone (4.12 ng/mg), desethylamiodarone (5.29 ng/mg) and MA (7.63 ng/mg). MA pellets in gastrointestinal tract were consistent with the autopsy conclusion, i.e., fatal intoxication due to in corpore pellet rupture in a body packer (the victim was initially deemed to have died from heart failure). In the absence of available data in the literature, amiodarone and metabolite presence in hair could putatively be the consequence of a chronic treatment. MA hair concentration was similar to those observed in regular consumers. However, interpreting this hair result is challenging due to (i) the possibility of contamination by sweat at the time of death, and (ii) the probable contamination by putrefaction fluids. This latter hypothesis (artifactual contamination during the postmortem postmortem) is highly supported by high concentration of MA in decontamination bath, and even more by the absence of the major MA metabolite (amphetamine) in hair. As a conclusion, in this particular situation, the hair analysis result (presence of MA and concomitant absence of amphetamine) is in agreement with the previously established cause of death.